Computational Study of Coal Particle Distribution in Coal Pulverizer: Effect of Air Flow Rate and Coal Particle Flow Rate - Why E.; Alnaimi F.; Hasini H.; Nasif M. (EDP Sciences, 2023)
Air; Coal; Computational fluid dynamics; Flow rate; Grinding mills; Thermoelectric power plants; Air flow-rate; Air/fuel ratio; Coal particles; Combustion of coal; Computational studies; Modelling and validation; Thermal power plants; Turbulence intensity; Coal combustion